Pengaruh Playdough Terapi Terhadap Penurunan Perilaku Agresif Anak Pra Sekolah Selama Hospitalisasi di Ruang St Theresia Rs Panti Nirmala Malang - Nurul Anjarwati; Lembah Andriani; Nurwidyaningtyas, Wiwit; Fitri Dwi Astuti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Preschool- age children accept hospital admission with fear. Several measures have been widely recommended to minimize the impact of hospitalization, but until now the most widely used and believed to be most effective is with play therapy. In preschool, one type of game is skill play, where this type of game uses motor skills. One of the skill play games is playing playdough. This study have the purpose was to determine the Effect of Playdough Therapy on Reducing Aggressive Behavior of Preschool Children During Hospitalization in the St. Theresia Room of Panti Nirmala Hospital Malang. The research design used Pre- Experimental Design with the Pretest-Posttest with Control Group Design, the sampling technique used was purposive sampling as many as 20 respondents on intervention group and control group. Analysis test on the Mann Whitney, the result was a significant difference between the aggresive level score of the control group pre-test and the treatment group (p=0.002< 0.05), the aggressive level score of the control group and the treatment group (p = 0.001< 0.05). Based on the results of the Wilcoxon test, it shows a significant difference in the level of aggressiveness (p = 0.000< 0.05). So, it can be concluded that the administration of playdough therapy in pediatric patients is very necessary to reduce aggressiveness due to hospitalization in children